Sublethal Effects of Polystyrene Nanoplastics on the Embryonic Development of Artemia salina (Linnaeus, 1758) - Martina Contino; Greta Ferruggia; Stefania Indelicato; Roberta Pecoraro; Elena Maria Scalisi; Antonio Salvaggio; Maria Violetta Brundo (Animals, 2023)
Currents, wave motion, solar radiation, and abrasion are mechanisms responsible for the degradation of large plastic artifacts and contribute to the dispersion of micro and nanoplastics into aquatic ecosystems, which are, currently, the most dangerous threats due to their invisibility and persistence. The present work evaluated the possible lethal and sublethal effects of amino-modified polystyrene nanoplastics (nPS-NH2) with diameters of 50 nm and 100 nm on Artemia salina (A. salina), an organism at the base of the trophic chain of the aquatic system, using a widely used model for the analysis of embryotoxicity from environmental pollutants. For this purpose, after evaluating the biodistribution of nanoplastics in the body of the tested animals, several endpoints such as anomalies, apoptosis, and ROS production were assessed. In addition, particular attention was dedicated to evaluating the correlation between toxicity and the particle size tested. The results reported that, despite the absence of a lethal impact, several sublethal effects involving gut and body size malformations, as well as the enhancement of apoptosis and oxidative stress in relation to an increase in tested concentration and a decrease in nanoparticle size.